In vitro evaluation of the effect of core thickness and fabrication stages on the marginal accuracy of an all-ceramic system. - F Farid; H Hajimiragha; R Jelodar; A S Mostafavi; H Nokhbatolfoghahaie (Tehran University of Medical Sciences, 2012)
To evaluate the influence of core thickness and fabrication stages on the marginal accuracy of IPS e.max Press crowns.Twenty IPS e.max Press crowns, 1.5mm thick, were fabricated on metal dies. The crowns had two different core thicknesses, 0.8mm for group A and 1mm for group B, ten for each group. Marginal gap was measured after each stage of core fabrication, veneering and glaze firing. The specimens were not cemented and the measurements were made at four points on metal dies using a stereomicroscope (×120). Data were analyzed by SPSS software and independent t-test.Mean marginal gaps measured after each stage for group A were 13.5 (±1.4) μm, 33.9 (±2.3) μm and 40.5(±1.7) μm, and for group B these figures were 14.9(±2.0) μm, 35.5(±2.2) μm and 41.3(±2.0) μm. There were no statistically significant differences in marginal gap values between the two groups (p>0.1). Significant increase in gap was observed after the veneering stage in both groups (p